2018
DOI: 10.5812/ircmj.16231
|View full text |Cite
|
Sign up to set email alerts
|

Well-Being, Mental Health, General Health and Quality of Life Improvement Through Mindfulness-Based Interventions: A Systematic Review and Meta-Analysis

Abstract: Context: Mindfulness-based interventions have shown promising therapeutic outcomes in improving well-being, mental health, general health, and quality of life, however, findings in this regard are inconsistent. The present study aimed at clarifying this inconsistency in the literature focusing on the Iranian studies through a systematic review and meta-analysis study. Evidence Acquisition: The databases of Pubmed, Scopus, Doaj, EBSCO, Iranmedex, MagIran, SID, and Comprehensive Human Sciences Portal, and additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…Numerous studies have examined the effectiveness of psychological intervention programs, including cognitive behavioral therapy, interpersonal psychotherapy, and mindfulness interventions . In particular, the mindfulness‐based interventions have shown promise for treating or preventing diverse psychological problems, as well as for relieving pain and improving well‐being . In recent years, a number of mindfulness programs (eg, mindfulness‐based childbirth and parenting education and mindfulness‐based childbirth education) integrated prenatal education and mindfulness training, most of which have reported reduced rates of anxiety, depression, and stress during pregnancy and have improved childbirth self‐efficacy and mindfulness .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have examined the effectiveness of psychological intervention programs, including cognitive behavioral therapy, interpersonal psychotherapy, and mindfulness interventions . In particular, the mindfulness‐based interventions have shown promise for treating or preventing diverse psychological problems, as well as for relieving pain and improving well‐being . In recent years, a number of mindfulness programs (eg, mindfulness‐based childbirth and parenting education and mindfulness‐based childbirth education) integrated prenatal education and mindfulness training, most of which have reported reduced rates of anxiety, depression, and stress during pregnancy and have improved childbirth self‐efficacy and mindfulness .…”
Section: Introductionmentioning
confidence: 99%
“…Mindfulness-based interventions (MBIs) therefore have been established to facilitate formal (e.g., breathing, sitting, walking, body scan) or informal (e.g., mindfulness in everyday life) practices to cultivate moment-by-moment awareness of thoughts, feelings, bodily sensations [ 7 ]. The two most widely adopted MBIs, mindfulness-based stress reduction (MBSR) [ 8 ] and mindfulness-based cognitive therapy (MBCT) [ 9 ] have been shown to be efficacious, particularly in improving mental health, general health, and quality of life [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have found that mindfulness-based interventions are an effective way to improve medical and psychological symptoms and conditions, as well as to improve general health, anxiety, and anger ( Hirano and Yukawa, 2013 ; Aghaie et al, 2018 ; Guo et al, 2019 ; El Morr et al, 2020 ; Shepherd, 2020 ; Burgess et al, 2021 ; Takebe and Sato, 2021 ). The results of a systematic review and meta-analysis on the effect of mindfulness-based interventions on wellbeing, mental health, and general health showed that the mindfulness-based interventions had a large effect size on wellbeing, mental health, and general health ( Aghaie et al, 2018 ). Karing (2021) reported that mindfulness, along with optimism, was one of the two most relevant protective factors against anxiety.…”
Section: Introductionmentioning
confidence: 99%